2018
DOI: 10.1186/s12889-018-5741-x
|View full text |Cite
|
Sign up to set email alerts
|

Know where to go: evidence from a controlled trial of a healthcare system information intervention among immigrants

Abstract: BackgroundImmigrants may face problems with accessing the Danish healthcare system due to, for example, lack of knowledge of how to navigate it, which may cause inappropriate healthcare-seeking. Danish municipalities provide a mandatory introduction and language programme for newly arrived immigrants, but no information on the healthcare system is offered. This study investigated what effects information about the Danish healthcare system may have on the hypothetical healthcare-seeking behaviour of newly arriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…They received the aforementioned items in standard program as well as embedded health content whereas HL changes were not significantly different when the two groups were compared [35]. Jervelund et al [24], investigated healthcare-seeking behavior before and after an information intervention among immigrants, results showed that actual healthcare use of immigrants didn’t change after receiving either a course or written information on the Danish healthcare system of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…They received the aforementioned items in standard program as well as embedded health content whereas HL changes were not significantly different when the two groups were compared [35]. Jervelund et al [24], investigated healthcare-seeking behavior before and after an information intervention among immigrants, results showed that actual healthcare use of immigrants didn’t change after receiving either a course or written information on the Danish healthcare system of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…For this group, health-related aspects could be effectively embedded to appropriate activities, i.e. language school programs [13]. Healthcare professionals should be trained in cultural sensitivity and have skills in communications to improve seeking medical care and vaccination rates [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results underscore the need for further improvement and development of educational interventions, as well as ensuring adequate utilization of healthcare services in other ways. 29 Furthermore, the irregular use of healthcare services by migrants is much lower than that of Spanish citizens (as well as documented migrants), The relationship between limited CHL and EHL was found to be related to underutilization of the internet and a lack of recognition of its importance.…”
Section: Methodsmentioning
confidence: 98%